2 + 3 = 10

7 + 2 = 63

6 + 5 = 66

8 + 4 = 96

Then:

9 + 7 = ????

### 2 Answers | Add Yours

The first thing you need to do is find a pattern in the four equations you have been given.

equation 1) 2 + 3 = 10

If you add 2 + 3 you get 5, 10 (the given answer) divided by 5 (the sum of the 2 digits) equals 2 (which is the first digit)

equation 2) 7 + 2 = 63

If you follow the pattern from equation 1, you would add 7 and 2 then multiply by the first digit 7. 7 + 2 = 9 * 7 = 63 This answer checks

equation 3) 6 + 5 = 66

If you follow the pattern from eqaution 1, you would add 6 and 5, then multiply by the first digit 6. 6 + 5 = 11 * 6 = 66 This answer checks

equation 4) 8 + 4 = 96

If you follow the pattern from equation 1, you would add 8 + 4 then multiply by the first digit 8. 8 + 4 = 12 * 8 = 96 This answer checks

question 9 + 7 = ??

Following the pattern from equations 1 -4, you need to add the first 2 digits and then multiply by the first digit. 9 + 7 = 16 * 9 = 144.

I hope this helps with future problems that are similar

Strictly speaking the equations given in the question are incorrect. We cannot have sum of 2 and 5 as 10. However if we consider the equations given not as normal mathematical equations but as some different method of representing functions of two numbers 'a' and 'b' where the sign '+' represents this function, we can see a common pattern in the equation given:

We see that

2 + 3 = 10 = sum of 2 and 3, multiplied by 2.

7 + 2 = 63 = sum of 7 and 2, multiplied by 7.

6 + 5 = 66 = sum of 6 and 5, multiplied by 6.

8 + 4 = 86 = sum of 8 and 4, multiplied by 8.

This can be represented in general terms as

a + b = sum of a and b, multiplied by a.

Using this general relationship:

9 + 7 = sum of 9 and 7, multiplied by 9 = 144

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes